2002
DOI: 10.1046/j.1365-3083.2002.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Interleukin‐1β and Interleukin‐1 Receptor Antagonist Genes and Malaria in Ghanaian Children

Abstract: We have investigated the possible associations between polymorphisms in two interleukin-1 (IL-1) genes and severity of Plasmodium falciparum malaria in Ghanaian children with cerebral malaria, severe anaemia or uncomplicated malaria and controls. There was no significant difference in genotype and allele frequencies in IL-1b exon 5 or interleukin-1 receptor antagonist (IL-1ra) polymorphisms between the studied groups, suggesting that the two polymorphisms may not be involved in the pathogenesis of severe malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
3
13
1
Order By: Relevance
“…Alternatively, genetic differences in IL-1ra receptors or genes between the two populations might affect IL-1ra production differently in children with CM in West African vs. East African populations. Although studies in Thailand [12] and Ghana [13] have not demonstrated an association between IL-1ra polymorphisms and disease severity within the populations, differences might still exist between populations that affect IL-1ra responses and disease severity. In the present study, IL-1ra levels also remained associated with mortality after adjustment for G-CSF and MCP-1 levels, although the association was not particularly strong (P=0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, genetic differences in IL-1ra receptors or genes between the two populations might affect IL-1ra production differently in children with CM in West African vs. East African populations. Although studies in Thailand [12] and Ghana [13] have not demonstrated an association between IL-1ra polymorphisms and disease severity within the populations, differences might still exist between populations that affect IL-1ra responses and disease severity. In the present study, IL-1ra levels also remained associated with mortality after adjustment for G-CSF and MCP-1 levels, although the association was not particularly strong (P=0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that a locus in the IL1 gene cluster is involved in control of parasite levels, reflected in alterations of both specific and total antibodies. Polymorphisms in the IL1 gene cluster have been investigated for associations to both severe and mild malaria [8,9], with a polymorphism in IL1B (IL1B ϩ3953 *T) being associated with both parasitemia [8] and severe malaria [9], although no previous associations have been observed with IL1RN [8,9]. There was some evidence for an association between IL10 SNPs and haplotypes and Th2 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Because significant LD was not observed between IL1B and IL1RA in the present study, we cannot exclude the possibility that polymorphisms in the other IL1 family genes located between IL1B and IL1RA , such as IL1 family member 9 ( IL1F9 ) and IL1 family member 8 isoform 1 ( IL1F8 ), are associated with cerebral malaria. It is currently unknown whether associations between IL1 B 3953C>T and cerebral malaria [5] or parasitemia [6] in African populations result from a LD with other functional polymorphisms in this chromosomal region. Thus, further studies of various populations are required to clarify whether polymorphisms of IL1 family genes are involved in the pathogenesis of cerebral malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the IL1B 3953C>T polymorphism, which lies in exon 5 of IL1B , was reported to be associated with cerebral malaria in Gambia [5]. Gyan et al [6] reported that, in Ghanaian Children, levels of parasitemia were significantly higher in uncomplicated malaria patients possessing the IL1B 3953T allele ( i.e ., 3953T/T and 3953C/T genotypes) than those possessing only 3953C ( i.e ., 3953C/C genotype), although this polymorphism and the IL1RA variable number of tandem repeat (VNTR) polymorphism were not associated with cerebral malaria.…”
Section: Introductionmentioning
confidence: 99%